Association between migration and physical activity among medical students from a university located in Lima, Peru - Zevallos, Alejandro (2019)
Objective To evaluate the association between migration and physical activity among medical students from a university located in Lima, Peru. Methods A cross-sectional study was conducted among second-year medical students from a Peruvian university. Data on moderate- to vigorous-intensity physical activity (MVPA) and migration features were obtained through a self-report questionnaire. To assess the associations of interest, prevalence ratios (PR) along with their 95% confidence intervals (95% CI) were calculated using Poisson regression with robust variances.